Analysis of Mathematics Literacy Ability Observed from Metacognition in Learning Realistic Synectics Assisted by Schoology - Hidayat, Yodie Nur; Wardono, Wardono; Rusilowati, Ani (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe the ability of mathematics literacy in terms of students' metacognition in learning realistic synectics assisted by schoology. The subjects chosen by random sampling in this study were 32 students of class VII A of SMP Negeri 4 Adiwerna in the 2018/2019 academic year. Data analysis using Mix Method with Quasi Experimental Design. The results showed that with the learning of realistic synectics assisted by schoology, students’ mathematical literacy skills in terms of metacognition is varied. Based on 7 students with high metacognition, obtained 6 students with high mathematical literacy skills and 1 student with moderate mathematical literacy abilities. Of the 21 students with moderate metacognition obtained 5 students with high mathematical literacy skills, 12 students with moderate mathematical literacy abilities and 4 students with low mathematical literacy abilities. Of the 4 students with low metacognition all of them had low mathematical literacy skills as well.